Chemical state of radioiodine formed by fast neutrón activation of solid CsIO4 and CsCIO4 - Dupetit, Gustavo Alberto (1967)
Fil: Dupetit, Gustavo Alberto Comisión Nacional de Energía Atómica; Argentina